(untitled) (IJM: Journal of Multidisiplinary, 2025)
Finance plays a crucial role in a company, as every strategic decision from budget allocation to investment planning is based on accurate financial information and analysis. Behind the importance of this function, however, lies the everpresent risk of financial fraud. The application of business ethics becomes an inseparable foundation for suppressing both the intent and opportunity for fraud. By internalizing the values of honesty, integrity, and responsibility throughout every level of the organization, a company can foster a culture of transparency that builds trust among employees and external stakeholders alike. This study seeks to explore the role of business ethics in preventing financial fraud by examining previous literature and expert opinions. Through a literature review methodology, data and findings from various journals are analyzed in depth to conclude that business ethics are not merely written guidelines, but a tangible foundation which, when implemented consistently, will strengthen a company’s internal control systems, protect its reputation, and ensure the sustainability of operations over the long term.